Enhancing tourists' safety in volcanic areas: An investigation of risk communication initiatives in Iceland. (November 2020) - Bird, Deanne K.; Gísladóttir, Guðrún
Abstract: Providing accurate and timely hazard warnings to residents in Iceland is a difficult task despite authorities being familiar with the at-risk population. A more challenging task is communicating that same information with a transient population i.e., the increasing number of tourists who visit Iceland and engage in activities on and around Iceland's volcanoes. Increased tourism results in greater numbers of tourists exposed to potentially harmful and life-threatening situations. To enhance awareness of these potential situations, authorities rely on risk communication initiatives. This paper examines people's perceptions and beliefs with respect to risk communication initiatives and, behaviour in volcanic environments. Data informing this research was captured through focus group discussions, interviews and questionnaire surveys in a longitudinal study conducted from 2009 to 2017 and involved a range of stakeholders: tourists, tour guides and operators, local police, government officials, rescue team members, local residents and, disaster risk reduction academics, practitioners and professionals. The aims of interrogating these datasets are to: 1) identify whether risk communication initiatives are enhancing or have the potential to enhance tourists' safety and 2) provide evidence-based recommendations to inform the continual improvement of risk communication strategies within the tourism sector. This work is critical given the economic significance of tourism in Iceland and the frequency of volcanic eruptions and other natural hazard events. The results suggest that while these initiatives are reaching some people, they are not accessible to the majority and are therefore ineffective, in their current form, at enhancing tourists' safety. The results also show that tourists are generally not risk averse, highlighting the considerable challenges communicators face. In light of these challenges, we must continually strive to ensure that tourists are well equipped to make informed decisions to prevent injury and fatality. It is imperative that the sector as a whole is actively involved in risk reduction strategies. This includes long-term and ongoing commitment to regularly distributing consistent hazard, risk and response information through all available channels so that when a warning is issued it does not come as a surprise; and, ensuring risk communication information and tools meet the needs of the intended audience. The importance of this research extends beyond Iceland's volcanic environment, given the occurence of death and injury associated with nature-based tourism worldwide. To enhance tourists' safety, governments and the tourism sector as a whole, must invest greater resources and commitment to ensure tourists have access to accurate and up-to-date information so they can make informed decisions about their travel choices.